(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
General anesthesia plays a crucial role in pediatric dentistry, enabling comprehensive dental care for children with profound dental anxiety, developmental disabilities, extensive treatment needs, or behavioral management difficulties. This article examines the importance of safety considerations, collaborative care approaches, patient and parent education strategies, and emerging trends and best practices in pediatric dental anesthesia. Through a multidisciplinary approach involving dental, anesthesia, and other healthcare professionals, general anesthesia facilitates safe, effective, and comfortable treatment experiences for pediatric patients. Key considerations include pre-operative assessment, airway management, continuous monitoring, emergency preparedness, and post-operative care. Collaboration, patient-centered care, advanced anesthesia modalities, technology integration, and ongoing education and research are essential for optimizing outcomes and promoting oral health and overall well-being in pediatric patients undergoing dental procedures under general anesthesia.